2023
DOI: 10.1101/2023.03.06.23286791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Barriers and Enablers for the Equitable and Accessible Informed Healthcare Consent Process for People with Intellectual Disability: A Systematic Literature Review

Abstract: Objective To identify the factors that act as barriers to, or enablers of, proper informed consent for healthcare interventions for people with intellectual disability. Design Systematic literature review. No funding sources or conflicts of interest are reported. Data sources Databases: Embase, MEDLINE, PsychINFO, PubMed, SCOPUS, Web of Science, and CINAHL (last searched January 2022). Additional articles were obtained from an ancestral search of included articles and hand-searching of three journals. Eligibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Much of the efforts to making health information accessible focus on producing information in ‘easy read’ format, which consists of short, simple sentences with accompanying pictures. However, there is a lack of high-quality research evaluating the effectiveness of easy read information, despite the frequency of its use 12–14…”
Section: The Importance Of Reasonable Adjustmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the efforts to making health information accessible focus on producing information in ‘easy read’ format, which consists of short, simple sentences with accompanying pictures. However, there is a lack of high-quality research evaluating the effectiveness of easy read information, despite the frequency of its use 12–14…”
Section: The Importance Of Reasonable Adjustmentsmentioning
confidence: 99%
“…The paper by Dunn and colleagues [15] in this issue of BMJ Quality & Safety, is welcome new contribution to the literature, furthering our understanding of how to make the process of obtaining healthcare consent for people with an intellectual disability more equitable and accessible. The authors identified the barriers and enablers to obtaining healthcare consent by analysing 23 studies in a systematic review of the literature.…”
Section: Barriers and Enablers To Engagement In Decision-making About...mentioning
confidence: 99%
“…People with intellectual disability continue to experience high levels of stigma, resulting in a denial of equal rights, psychological distress ( 14 , 15 ), and a disproportionately high risk of physical, sexual, emotional, financial, and disability-related abuse ( 16 , 17 ). This extends to healthcare settings, and GeneEQUAL co-researchers shared their adverse and often traumatic experiences of neglect and abuse, including not having the opportunity to make their own healthcare decisions, being ignored when they present with a support person, and feeling pressured to provide consent ( 18 ). In Australia, the 2023 Royal Commission into Violence, Abuse, Neglect and Exploitation of People with Disability (the Disability Royal Commission) found ongoing systemic neglect and abuse of people with intellectual disability within the health system ( 19 ).…”
Section: Stigma and Abuse In Healthcarementioning
confidence: 99%